PENERAPAN MODEL INKUIRI TERBIMBING UNTUK MENINGKATKAN AKTIVITAS, HASIL BELAJAR DAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS X IPA.3 SMA NEGERI 3 BENGKULU TENGAH - Syafa’atin Noviana; Connie Connie; Dedy Hamdani (UNIB Press, 2017)
This study aims to describe the improvement of learning activity, learning outcomes and critical thinking skill of students by applying a model of guided inquiry. This research was conducted in four stages: planning, implementation, observation, and reflection. Subyek in research is all student in this class X IPA.3 aggregate 30 person. The results showed that students learning activity at cycle I with average score of 31 (good), cycle II of 33 (good), cycle III of 34,5 (good) and cycle IV of 35,5 (good). Student learning outcomes obtained the average grade score and classic learning completeness in the cycle I of 69,14 (enough) and 51,72% (unfinished), cycle II of 73 (enough) and 56,67% (unfinished), cycle III of 74,83 (enough) and 66,67 (unfinished) and cycle IV of 80,83 (good) and 80% (complete). For students’ critical thinking skill, that is: indicator focus questions cycle I of 70,69%, cycle II of 78,45%, cycle III of 81,89% and cycle IV of 83,62% (very critical), indicator consider the credibility of a source cycle I of 67,24%, cycle II of 73,28%, cycle III of 76,72% and cycle IV of 80,17% (critical), indicator deduce and consider the results of deduction cycle I of 56,89%, cycle II of 57,75%, cycle III of 60,34% and cycle IV of 63,79% (critical), indicator define terms and consider a definition cycle I of 69,83%, cycle II of 77,58%, cycle III of 79,31% and cycle IV of 81,89% (critical), and indicator define an action cycle I of 58,62%, cycle II of 61,21%, cycle III of 72,41% and cycle IV of 76,72% (critical). Based on the result of the research, it can be concluded that the implementation of guided inquiry model can improve the learning activity, learning outcomes and student critical thinking skills.